Charge and Spin Currents in Ferromagnet-Insulator-Superconductor Tunneling Junctions Using Hg-1223 High-Tc Superconductor. (25th August 2014) - Kitamura, Michihide; Uchiumi, Yoshitaka; Irie, Akinobu
Abstract : Charge and spin currents along thec -axis in ferromagnet-insulator-superconductor (F/I/S) tunneling junctions have been studied within the framework of the tunneling Hamiltonian model. As a superconductorS, HgBa2 Ca2 Cu3 O8+ δ (Hg-1223) withδ = 0.4 copper-oxide high-T c superconductor has been selected, and as a ferromagnet F, Fe metal with bcc structure has been selected for simplicity. The electronic structures of above materials have been calculated on the basis of the band theory using the spin-polarized self-consistent-field data for the atomic orbital energies and the universal tight-binding parameters (UTBP) for the interactions. For theη ↑ andη ↓ ( = 1 - η ↑ ) defined in the present paper, which are tunneling probabilities of the majority and the minority spin electrons, it is shown that the conditionη ↑ = η ↓ means the standard F/I/S tunneling junction with a nonmagnetic insulating layer, and the conditionη ↑ ≠ η ↓ means the F/I/S tunneling junction with a magnetic insulating layer showing a detectable magnetization. We have found that the charge current and the differential conductance nearly remain the same as the change ofη ↑, but the spin current is largely changed due to the change ofη ↑ . As an experimental method to detect the change of the spin current, the validity of an X-ray magnetic circular dichroism (XMCD) has been pointed out.